PENGGUNAAN MEDIA PERMAINAN KARTU KWARTET UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN IKATAN KIMIA DI KELAS X MIA SMA PGRI PEKANBARU - Mutiara Neldi; Herdini '; Roza Linda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to find out the improveret of student achievement of applying quartet card game media on chemical bonding subject in class X MIA at SMA PGRI Pekanbaru . Type of this research is experimental by Randomized Control group pretest-posttest Design. The population is all class X MIA SMA PGRI Pekanbaru that consists of 2 classes. Sample in this research consisted of two grade obtained after the test of normality and homogeneity, are class X MIA1 and X MIA2. The experimental class was applied with quartet card game media and control class by traditional learning. The data was analysed using test Mann-Whitney U with significance level (α=0,05) and dk =50. Based on the analysis and processing of data obtained zcount>ztable is 2.09>1.96, this mean that the application of the media quartet card game can improve the student learning Achievement on the subject of Chemical bonding in the of X class of MIA SMA PGRI Pekanbaru.Key words : Learning Achievement , Media Quartet Card game, Chemical bonding